Concentrations of 6-Benzylaminopurine (BAP) in micropropagation of banana ‘Farta Velhaco’ (AAB) - Pereira, Gustavo Alves; Santaella, Marcilio Broboff; Alves, Lefayete Michele Santana Montenegro; Silva, Elder Cassimiro; Flenga, Aparecida Islayne Silva; Santos, Danilo Marcelo Aires (Comunicata Scientiae, 2018)
Propagation methods such as in vitro micropropagation have been developed and improved to increase the multiplication rate in a short time and improve the seedlings quality. The objective of this study was to evaluate the efficiency of the different BAP concentrations on micropropagation of ‘Farta Velhaco’ banana during in vitro multiplication phase. The treatments were: T1 – control (0 mg L-1); T2 - 0.5 mg L-1; T3 - 1 mg L-1; T4 - 1.5 mg L-1; T5 - 2 mg L-1; T6 - 2.5 mg L-1; T7 - 3.0 mg L-1; T8 - 3.5 mg L-1 and T9 - 4.0 mg L-1 of BAP added to the MS culture medium. The total number of shoots produced per explant initial subculture every 30 days was evaluated. The highest number of shoots is recorded 2.5 mg L-1 BAP concentration, which promotes 3 shoots per explant in the 4th subculture. The 4.0 mg L-1 BAP concentration reduces the number of shoots.